Fresno-Merced Counties Legal Services Christmas Party at Patience Milrod's Home - Watkins, Howard::::::::: (1980)
Cindy Calvert reading her card; Scott Williams, Faheem Hameed, Patience Milrod, Joe Mendez, Marilyn Williams, Janice Pearson 3400 Block of E. Montecito Avenue